Flow intermittence and ecosystem services in rivers of the Anthropocene. Issue 1 (26th June 2017) - Datry, Thibault; Boulton, Andrew J.; Bonada, Núria; Fritz, Ken; Leigh, Catherine; Sauquet, Eric; Tockner, Klement; Hugueny, Bernard; Dahm, Clifford N.
Abstract: Intermittent rivers and ephemeral streams (IRES) are watercourses that cease flow at some point in time and space. Arguably Earth's most widespread type of flowing water, IRES are expanding where Anthropocenic climates grow drier and human demands for water escalate. However, IRES have attracted far less research than perennial rivers and are undervalued by society, jeopardizing their restoration or protection. Provision of ecosystem services by IRES is especially poorly understood, hindering their integration into management plans in most countries. We conceptualize how flow intermittence governs ecosystem service provision and transfers at local and river‐basin scales during flowing, non‐flowing and dry phases. Even when dry or not flowing, IRES perform multiple ecosystem services that complement those of nearby perennial rivers. Synthesis and applications . Conceptualizing how flow intermittence in rivers and streams governs ecosystem services has applied a socio‐ecological perspective for validating the ecosystem services of intermittent rivers and ephemeral streams. This can be applied at all flow phases and in assessing impacts of altered flow intermittence on rivers and their ecosystem services in the Anthropocene. Abstract : Conceptualizing how flow intermittence in rivers and streams governs ecosystem services has applied a socio‐ecological perspective for validating the ecosystem services of intermittent rivers and ephemeral streams. This can be applied at all flow phases and in assessing impacts of altered flow intermittence on rivers and their ecosystem services in the Anthropocene.